COVID-19 Unmasked: trajectories, risk and protective factors for mental health outcomes in young Australian children during the first year of the COVID-19 pandemic - Mira Vasileva; Eva Alisic; Vanessa E. Cobham; Tahlia Gash; C. M. Hoeboer; Elisabeth Hoehn; Sonja March; Caroline Donovan; Christel M. Middeldorp; Rebecca Moore; Alexandra De Young (Australian Journal of Psychology, 2025)
Objective Emerging evidence suggests a negative impact of COVID-19 on children’s mental health. The aims of this study were to examine trajectories of mental health in children younger than 6 years as well as risk and protective factors during the first year of the pandemic.Method In a prospective, longitudinal online study, data were collected on N = 837 children aged 1 to 5 years in Australia between May and July 2020 and after 3, 6 and 12 months, with n = 257 participating at all 4 timepoints. Individual trajectories ofanxiety, anger/irritability, depressive symptoms and sleep disturbance were analysed using latent growth mixture modelling.Results The results showed that 1 in 4 children experienced moderate to severe symptoms in each problem domain. The overall means for depressive symptoms, anger/irritability, and sleep disturbance decreased while anxiety increased over time. For most outcomes, two individual trajectories were identified: moderate/high-decreasing (26–29%) andlow-increasing. Important predictors were negative COVID-19 related impact on daily life, caregiver distress, lower child positive affect and self-regulation.Conclusions The current results highlight that the pandemic indirectly affected young children’s mental health, especially in the presence of risk factors such as caregiver distress and poor child self-regulation skills.